Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M205 - Torben Riehl; Nico Augustin; Mia Schumacher (PANGAEA, 2025)
Raw multibeam bathymetry data were collected aboard RV METEOR during cruise M205 using a 12kHz Kongsberg EM 122 multibeam echosounder with 2°x2° beam width. The expedition took place during 2024-10-23 – 2024-11-28 from Las Palmas (Spain) to Fortaleza (Brasil) in the Central Atlantic. The major aims of M205 "RUBBLE" — Rocky seafloor – Under-estimated driver for Benthic Biodiversity Living in the abyss and its Evolution — investigated the relationship between habitat heterogeneity and abyssal benthic biodiversity through quantitative and qualitative seafloor sampling in the eastern Vema Fracture Zone. Data were recorded outside EEZ in international waters. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by Senckenberg am Meer and GEOMAR Helmholtz Centre for Ocean Research, provision of the data is supported by the DAM Underway Project and published according to the FAIR principles. The expedition M205 was made possible through funding for the RUBBLE project from the German Research Foundation (DFG) and the Federal Ministry of Education and Research (BMBF) under grant no. GPF 21-1_060.